2006
DOI: 10.1590/s1678-77572006000200001
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of acellular dermal matrix graft evaluated in culture of murine macrophages

Abstract: The acellular dermal matrix allograft has been used as an alternative to autogenous palatal mucosal graft. The aim of this study was the evaluation of the biocompatibility of an acellular dermal matrix (AlloDerm®) in culture of macrophages. For hydrogen peroxidase determination we used the method of Pick & Kesari, and the Griess method for nitric oxide determination,. Statistical analysis showed no significant difference (p ≤ 0,05) in the release of nitric oxide and hydrogen peroxide by the macrophages exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…The release of NO and H2O2 as positive control showed statistically significantly higher values in the LPS group than in the ADM group. In the study mentioned, it was observed that serum did not show any significant difference compared with the ADM group, indicating that it did not have a therapeutic effect in the study context [109].…”
Section: Acellular Dermal Matricesmentioning
confidence: 86%
“…The release of NO and H2O2 as positive control showed statistically significantly higher values in the LPS group than in the ADM group. In the study mentioned, it was observed that serum did not show any significant difference compared with the ADM group, indicating that it did not have a therapeutic effect in the study context [109].…”
Section: Acellular Dermal Matricesmentioning
confidence: 86%